Analisis Personal Branding Suwardi “Becak Lawu” sebagai Petarung MMA Indonesia ditinjau melalui Dramaturgi - Priscillia, Bernice; Setiawan, Albert Octavio (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Suwardi sees MMA as having an attraction and a desire to develop the potential of Indonesian athletes to compete in One Pride and even go international. Suwardi's self-actualization is built through his personal Instagram social media. This research aims to determine the impression management carried out by Indonesian MMA fighter Suwardi "Becak Lawu". In the analysis, the theory used is Erving Goffman's dramaturgical theory with two aspects, front stage and back stage. Using a descriptive qualitative research approach by collecting data through interviews with key informant Suwardi "Becak Lawu"and observation. The results of this research show that Suwardi is able to create an attractive front stage persona with his humorous and friendly nature and to strengthen his identity as a well-known Indonesian MMA fighter. Meanwhile, back stage, he feels a great sense of responsibility as a well-known Indonesian MMA fighter and family man as a husband and father. Apart from that, this research reveals that Suwardi represents personal branding with both responsibilities in his life as a person who are the same in the real and virtual worlds.